Antimicrobial activity of Moringa oleifera Lam. against staphylococcus aureus - Cunom, Mae Cecille Fungo (College of Home Economics, University of the Philippines, 2009)
ABSTRACT In the present study,the antimicrobial activity of the ethanolic extract of Moringa oleifera Lam. leaves against the food-borne pathogen Staphylococcus aureus was investigated through the agar diffusion method. The minimum inhibitory and bactericidal concentrations were also established through the broth dilution method. The Moringa oleifera leaf extract (100mg/ml) exhibited a zone of inhibition of 9.17 mm against Staphylococcus aureus. The minimum inhibitory concentration (MIC) was 45 mg/ml. The result showed that ethanolic extract of Moringa oleifera leaves has the potential to be incorporated to food systems as an antimicrobial agent to prevent Staphylococcal food poisoning. The MIC and MBC levels might vary in actual food applications and it might take higher levels of antimicrobial agents to inhibit foodborne bacteria. The MIC and MBC values established should serve as a guide for future studies relating to S. aureus and other Gram-positive pathogenic bacteria in food.